Issues of Recruitment and Rationale for Conducting Clinical Trials on Mutans Streptococci Suppression in Mothers - Walter A. Bretz; Odila P. S. Rosa; Salete M. B. Silva; Patricia Corby; Lisa Weissfeld; Walter J. Loesche (Hindawi Limited, 2010)
The aims of this study are (1) to describe issues related to recruitment of mothers participating in a clinical trial of transmission of mutans streptococci (MS) from mother to child in Bauru, Brazil and (2) to perform cross-cultural and temporal comparisons of levels of infection of the MS in mothers of Bauru. A total of 1422 mothers were visited at their domiciles. Cutoff levels for the MS were established at ≥105 CFU/mL saliva. The main reason for a mother not enrolling was not being highly infected by the MS, yet 76% of mothers presented with levels ≥105 CFU/mL saliva. Recent studies in industrialized countries showed a negative coefficient for linear tests indicating significant decline overtime in the levels of MS in mothers. Intercountry comparisons for mothers' salivary levels of the MS with the Bauru study as the reference revealed significant differences with studies conducted in the last two decades.